Balancing Intimacy and Trust in Audio Journalism - Lindgren, Mia (2025)
This thematic issue explores the complex relationship between intimacy and trust in audio journalism, particularly focusing on podcasting as it evolves as a medium. It examines how podcasting’s intimate format creates both opportunities and challenges for journalistic practice. The opportunities include enhanced storytelling capabilities, deeper audience connections, and the ability to address social justice issues more effectively, as demonstrated through various case studies from sports podcasting to investigative journalism. However, the studies also identify significant risks, including the potential for parasocial relationships to compromise journalistic integrity, the challenge of maintaining professional standards while fostering audience connection, and the possibility of reinforcing echo chambers rather than bridging societal divides. The research spans multiple geographical contexts, from Serbian podcasting in hybrid regimes to Chinese platforms, offering insights into how these dynamics manifest across different political and cultural frameworks. The collection of articles employs diverse methodological approaches, from theoretical frameworks combining cosmopolitan ethics with feminist ethics of care to empirical analyses of listener trust and content analysis of podcast platforms. Ultimately, the thematic issue suggests that as podcasting continues to mature, finding the right balance between personal connection and professional practice remains crucial for the medium’s development as a journalistic tool.